Constructing an inventory for fast screening of hydraulic and hydrologic performance of stormwater control measures. Issue 2 (25th November 2022) - Lerer, Sara Maria; Guidje, Alexandre Hallkvist; Drenck, Karin Margrethe Löf; Jakobsen, Camilla Christiane; Arnbjerg-Nielsen, Karsten; Mikkelsen, Peter Steen; Sørup, Hjalte Jomo Danielsen
Abstract: Stormwater control measures (SCMs) are effective and sustainable complementary means of managing stormwater in cities. Unlike underground drainage systems, they require space on the city surface, and therefore must be included in initial sketches of urban planning and design. These initial sketches are often made by architects and urban planners, who are usually not trained in hydrology, and therefore require simple and robust tools to inform their initial plans with respect to stormwater management. There may be local guidelines for dimensioning SCMs, but their applicability is often limited with regard to the range of SCMs, and the methodology behind them may be oversimplified, including a lack of assessment of benefits on the urban hydrological cycle. We developed a methodology for estimating multiple performance indicators of a wide range of SCMs and applied it to Danish meteorological conditions. The methodology includes consulting expected end users, configuring an SWMM model for each SCM type and choosing applicable parameter ranges, running multiple simulations for each type covering the parameter space, and post-processing the results using python and PySWMM. The outputs can be used to draw general recommendations regarding effective application ranges for different SCMs, and to quickly assess the performance of case-specific configurations. HIGHLIGHTS: An inventory was created for stormwater control measures' performance in Denmark. Performance was simulated using SWMM with carefully selected model parameters. The inventory contains tens of thousands of parametrizations and simulation results. The inventory can be used to quickly assess plausible performance of SCMs. The methodology can easily be adapted to other locations.